Smart specialization in a subnational context: Evidence from Greece - Kyriakos Drivas; Claire Economidou; Ioannis Kaplanis; Maria Theano Tagaraki (SPOUDAI - Journal of Economics and Business, 2021)
Regional domestic activity can provide valuable insights on whether these activities can fuel innovation activity of international impact. This paper provides an alternative strategy in measuring regional innovative activity based on the number of applications of various forms of Intellectual Property Rights (IPRs). Our analysis focuses particularly on Greek regions over the last two decades and documents a strong relationship between domestically- and internationally-filed IPRs. Class-level analysis, however, shows substantial heterogeneity across fields highlighting the role of smart specialization and in particular the usefulness of a regional innovation policy targeting on specific capabilities for each region. The fact that domestic patents and trademarks follow more closely the recent economic crises in Greece is also an issue we need to consider when operationalizing regional innovation policy.
Keywords: O34; O38; R11; 330; smart specialization; regional innovation; patents; trademarks